Numerical investigation of refractory lining thickness effects on shell temperature in the burning zone of cement rotary kilns - Alturki, Salwan F.; Ficzere, Péter (Design of Machines and Structures, 2025)
Cement kilns are energy-intensive systems where refractory insulation plays a critical role in minimising heat loss and controlling shell temperature. The burning zone, in particular, operates under extreme thermal conditions, making the design of the refractory lining essential for maintaining thermal efficiency. This study presents a comprehensive numerical investigation into the influence of refractory lining thickness on the thermal performance of the kiln shell in the burning zone. Steady-state finite element simulations were conducted using Solid Edge Simulation with NX Nastran solver and actual rotary kiln parameters to analyse five different refractory thicknesses (150mm, 175mm, 200mm, 225mm, and 250mm). A uniform temperature boundary condition representing the thermal load typical of the burning zone in cement kilns. Results demonstrated a clear inverse correlation between lining thickness and outer shell temperature. The 250mm lining yielded a minimum shell temperature of approximately 155°C, while the 150mm lining led to external temperatures exceeding 250°C. These findings highlight the significance of optimizing refractory lining design to enhance energy efficiency, reduce thermal losses, and ensure structural safety in cement kilns. This work contributes to better thermal management and informed maintenance strategies in the cement manufacturing sector.